1980
DOI: 10.1287/opre.28.4.1018
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note—An n-Constraint Formulation of the (Time-Dependent) Traveling Salesman Problem

Abstract: A new formulation of the time-dependent salesman problem is presented which uses n3 variables and only n constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 4 publications
0
56
0
Order By: Relevance
“…Either way, we can pick i, j ∈ {3, 5} with i = j such that i / ∈ S ′ , j ∈ S ′ . So pick an s-path that goes through vertices (1, 1), (2, 2), (4, 3), (i, 4), (j, 5), (7,6). Such an s-path satisfies (10) for S at equality and for S ′ as a strict inequality since it cannot use any arcs of A(S ′ , t) for any t.…”
Section: Theorem 12 If N ≥ 7 Then (10) Defines a Distinct Facet Of Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Either way, we can pick i, j ∈ {3, 5} with i = j such that i / ∈ S ′ , j ∈ S ′ . So pick an s-path that goes through vertices (1, 1), (2, 2), (4, 3), (i, 4), (j, 5), (7,6). Such an s-path satisfies (10) for S at equality and for S ′ as a strict inequality since it cannot use any arcs of A(S ′ , t) for any t.…”
Section: Theorem 12 If N ≥ 7 Then (10) Defines a Distinct Facet Of Pmentioning
confidence: 99%
“…Results for the STSP are surveyed in [13] and for the ATSP in [3]. Formulations for the TDTSP have been proposed or studied in [23,20,7,10,29,9]. Exact algorithms for the TDTSP are presented in [20,4,29] and, for the special case of the TDP, in [6,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Langevin et al [1990] showed that the LP relaxation of GG is equivalent to that of the two-commodity flow formulation proposed by Finke et al [1984] -hereafter FCG. Fox et al [1980] proposed three formulations for the time-dependent traveling salesman problem that are valid for the ATSP, as well. These formulations present n 3 binary variables, r ijk , that are equal to 1 if and only if arc (i, j) ∈ A is in position k in the optimal tour.…”
Section: Review Of Polynomial Formulationsmentioning
confidence: 99%
“…FISCHETTI, LA-PORTE, and MARTELLO (1993) presented an algorithm based upon dual ascent and gave computational results for the (optimal) solution of problems involving up to 60 cities. For earlier work on this problem, see PICARD and QUEYRANNE (1978), FOX et al (1980).…”
Section: Previous Workmentioning
confidence: 99%